(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Anita Desai is among the most distinguished and well-known Indian writers. Anita Desai was born on June 24, 1937, into a mixed-race family consisting of a Bengali father and a German mother. She was fluent in Hindi, English, Bengali, and German. Anita Desai nevertheless decided to write her children’s books, novellas, and novels in English. In the traditional sense, she is not a social realist. Her stories focus on man-woman interactions, marital problems, emotional struggles, loneliness, and a lack of communication. Anita Desai’s emphasis on the inner temperament of her characters sets her apart from other female authors. Her main objective is to depict the characters’ mental states at a critical exigency.